2001
DOI: 10.1103/physrevb.63.094506
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic contribution to the quasiparticle self-energy in systems with strong electron-phonon interaction

Abstract: We investigate effects of a nonadiabatic electron-phonon(boson) interaction on the quasiparticle self-energy in the lowest order in the coupling constant.Existing approaches either overestimate, or underestimate these effects because of different approximations for momentum and frequency dependences of the vertex corrections. The connection between the nonadiabaticity and a possible instability of the interacting Fermi system is discussed as well.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
2
21
1
1
Order By: Relevance
“…During last years quite a few numerical and analytical studies have confirmed this conclusion [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (and references theirein). On the other hand a few others (see, for example, [29,30]) still argue that the breakdown of the Migdal-Eliashberg theory might happen only at λ ≥ E F /ω >> 1. Indeed numerical study of the finite bandwidth effects [31] and some analytical calculations of the vertex corrections to the vertex function [32,33,30] with the standard Feynman-Dyson perturbation technique confirm the second conclusion.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During last years quite a few numerical and analytical studies have confirmed this conclusion [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (and references theirein). On the other hand a few others (see, for example, [29,30]) still argue that the breakdown of the Migdal-Eliashberg theory might happen only at λ ≥ E F /ω >> 1. Indeed numerical study of the finite bandwidth effects [31] and some analytical calculations of the vertex corrections to the vertex function [32,33,30] with the standard Feynman-Dyson perturbation technique confirm the second conclusion.…”
mentioning
confidence: 99%
“…On the other hand a few others (see, for example, [29,30]) still argue that the breakdown of the Migdal-Eliashberg theory might happen only at λ ≥ E F /ω >> 1. Indeed numerical study of the finite bandwidth effects [31] and some analytical calculations of the vertex corrections to the vertex function [32,33,30] with the standard Feynman-Dyson perturbation technique confirm the second conclusion. In this letter I compare the Migdal solution of the Holstein Hamiltonian with the exact one in the extreme adiabatic regime, ω/E F → 0, to show that the ground state of the system is a self-trapped insulating state with broken translational symmetry already at λ ≥ 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many works have been devoted to superconductivity in nonadiabatic systems and to constructing a theory extending beyond the Migdal theorem (see [7]). It follows from these investigations that for ε F ∼ ω 0 , the vertex functions become negative and therefore reduce the electron-phonon interaction constant, not leading to high values of the superconducting transition temperature T c .…”
Section: Introductionmentioning
confidence: 99%
“…обзор [7]). Из этих исследований вытекает, что вершинные функции при ε F ∼ ω 0 оказываются отрица-тельными и, следовательно, уменьшают константу электрон-фононного взаимодей-ствия, не приводя к высоким значениям температуры сверхпроводящего перехода T c .…”
Section: Introductionunclassified